Enhancement of subject description of fiction with annotations - Alenka Šauperl; Viktor Harej; Tanja Merčun; Tamara Jesenovec; Jelka Kastelic; Barbara Plestenjak; Uršula Vimer Kovaček (Knjižnica)
ABSTRACT